baru wrote:

Hi Bunuel ,

f(x)=(x−p)(x−q)

f(11)=f(20)

If I take p and q as 15.5 then also f(11) = F(20) , I was not given that p & Q are root .(x−p)(x−q)

F(11)=(11-15.5)(11.15.5) = F(20) = (20-11.5)(20-11.5)

Please correct me , I am confused .

You didn't consider f(11) = 0 and f(20) = 0.

_________________

MathRevolution: Finish GMAT Quant Section with 10 minutes to spare

The one-and-only World’s First Variable Approach for DS and IVY Approach for PS with ease, speed and accuracy.

"Only $149 for 3 month Online Course"

"Free Resources-30 day online access & Diagnostic Test"

"Unlimited Access to over 120 free video lessons - try it yourself"